Simulation of the start-up of a Hydro Power plant for the emergency power supply of a nuclear power station. - Lindenmeyer, D.
A hydro power plant and a nuclear power plant's auxiliaries are modeled using the Electromagnetic Transients Program (EMTP). The computer models allow for the simulation of a hydro generator start-up and the following energization of a nuclear power station's auxiliary motors under off-nominal voltage and frequency conditions. The paper describes the derivation of generator, turbine, exciter, and induction motor models, and their individual validation through field measurements. The complete power system model is verified by comparing simulation results to measurements, as obtained during an Engineered Safeguards Functions (ESF) test of the emergency power system of Oconee nuclear power plant
Keywords: EMTP; Electromagnetic Transients Program; Engineered Safeguards Functions; Oconee nuclear power plant; Auxiliary motors energisation; Computer models; Emergency power supply; Emergency power system; Exciter; Field measurements; Generator; Hydro generator start-up.; Hydro power plant start-up.; Induction motor models; Nuclear power station; Off-nominal frequency conditions; Off-nominal voltage conditions; Simulation; Turbine